The role of chicken management practices in children's exposure to environmental contamination: a mixed-methods analysis - Simone Passarelli; Ramya Ambikapathi; Nilupa S. Gunaratna; Isabel Madzorera; Chelsey R. Canavan; Ramadhani Abdallah Noor; Dagmawit Tewahido; Yemane Berhane; Simbarashe Sibanda; Lindiwe Majele Sibanda; Tshilidzi Madzivhandila; Bertha L. M. Munthali; et al. (BMC, 2021)
Abstract Background Household chicken production presents an opportunity to promote child nutrition, but the benefits might be offset by increased environmental contamination. Using household surveys, direct observations, and in-depth interviews with woman caregivers, we sought to describe the relationship between chicken management practices and household exposure to environmental contamination, and assess barriers to adopting improved husbandry practices. Methods First, we analyzed baseline data from 973 households raising chickens in the two interventions arms from the Agriculture-to-Nutrition (ATONU) study in Ethiopia to assess the relationship between animal management practices and environmental exposures. Second, we conducted six-hour direct observations of children's environmental exposures in 18 households. Among these households, we analyzed in-depth interviews with child caregivers. Results Quantitative analyses showed that households raised approximately 11 chickens, had animal feces visible on the property 67% of the time, and children's hands were visibly dirty 38% of the time. Households with more chickens had lower exposure to animal feces. Having a chicken coop increased the risk of observing animal feces on the property by 30%, but among those with a coop, having an enclosed coop reduced that risk by 83%. Coops that were enclosed, had fencing, and were located further from homes were associated with a reduced risk of observing animal feces and an increased likelihood of children having clean hands. Direct observations showed that chicken coops were often poorly designed or not used. On average, 3 to 5 chickens were inside homes at a time, and livestock and domestic animals were frequently inside of houses and interacting with young children. In-depth interviews revealed that protection of animals, maintenance of household cleanliness and health, type of chicken (local versus improved) and resource constraints influenced management decisions. Conclusions Improvements in chicken management practices could mitigate the exposure of household members to environmental contamination. Our findings highlight the need for training and resources to promote safe animal husbandry practices and optimal child health in nutrition-sensitive livestock projects. Trial registration Clinical trials number: NCT03152227 ; Retrospectively registered at ClinicalTrials.gov on May 12, 2012.